Multidimensional poverty in Silveira Martins/RS: an application of Alkire-Foster Method (AF) - Marin, Solange Regina; Glasenapp, Sirlei; Vieira, Carine; Diniz, Géssica Mathias; Porsse, Melody de Campos Soares; Ottoneli, Janaína (Revista de Administração da UFSM, 2018)
The Capability Approach, as proposed by Amartya Sen (1979, 1985, 1987, 1999a, 1999b), analyzes poverty beyond monetary income in considering dimensions as health, education, sanitation and others that are valued by people. From this proposal, Alkire and Foster (2007) have developed a method of measuring poverty that aggregates the various aspects of people’s lives in a multidimensional measure. The objective of this study is to explore the Alkire-Foster Method (AF) and present the general measurement obtained in a study in the city of Silveira Martins (RS). The final measure revealed that people are most deprived of the freedom enjoyed in the community, access to income, employment, basic services and education, which supports the senian view that poverty is beyond monetary income. Based on the AF Method, it is possible to formulate policies aimed at the dimensions in which many people suffer more deprivation.